Digital Financial Literacy dan Financial Stress and Hardship: Analisis Mediasi Positive Financial Behavior Using Digital Finance terhadap Financial Well-Being pada Pasangan Muda Muslim yang Menikah di Tangerang - Pratiwi, Aziizah Nur; Amri, Andi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
This study aims to determine and analyze Digital Financial Literacy and Financial Stress and Hardship: Mediation Analysis of Positive Financial Behavior Using Digital Finance on Financial Well-Being in Young Muslim Married Couples in Tangerang. This type of research uses quantitative with a causality approach using primary data in the form of questionnaires as a source of data collection. This study used Random Sampling of Young Muslim Married Couples in Tangerang with a total of 100 respondents. The data analysis technique used is SEM (Structural Equation Modeling) with the help of SmartPLS software version 4. The results showed that 1) DFL has no positive effect on FWB. 2) DFL has no positive effect on PFBUDF. 3) FSH has no positive effect on PFBUDF. 4) FSH has a positive effect on FWB. 5) PFBUDF has a positive effect on FWB. 6) PFBUDF does not play a significant role in mediating DFL and FWB. 7) PFBUDF plays a significant role in mediating FSH and FWB.